Pregnancy induced hypertension New Concepts. - Pacheco Romero, José (2015)
Pregnancy induced hypertension (PIH) is a disease that complicates pregnancy progressively and cunninggly, frequently carrying grave maternal and perinatal consequences. We now know PIH consists in a biochemical and histological endothelial disease, with predominance of contractile over relaxing substances and lability to vasopressor substances, as well as increment in mitogenic activity and abnormalities of clothing mechanisms. There is also decrease of plasma volume in direct relation with hypertension, decrease of erythrocyte deformability, and defective placentation, all showing immunologic and genetic features that would start with pregnancy. There is no premonitory analysis, but laboratory data can suggest severity of the disease. We should consider a diastolic blood pressure of 80 mm Hg as hypertension. Mother can help watch babys growth and activity in her uterus. Ultrasound examination establishes fetal development and wellbeing. In our country, magnesium sulfate and nifedipina are drugs of election to treat hypertensive crisis. We should not try to lower the diastolic blood pressure below 100 mm Hg to avoid worsening placental flow. Treatment of pregnancy induced hypertension is delivery of fetus and placenta, recalling that there is risk of convulsions and hypovolemic shock and disseminated intravascular coagulation in the immediate postpartum period. Prolongation of pregnancy might lead to maternal hypertension a few year later and hypertension and neurologic secuelae in the fetus. Management of the disease require, especialized care and knowledge of the pathophysiology of the disease as well as of the maternal and fetal consecuences. The author proposes reasons to modify the current classification of hypertensive diseases of pregnancy.